Arterial stiffness indexes and serum cytokine levels in seronegative spondyloarthritis: relationships between stiffness markers and metabolic and immunoinflammatory variables. (2nd November 2015) - Tuttolomondo, A; Pecoraro, R; Buttà, C; Di Raimondo, D; Ferrante, A; Della Corte, V; Ciccia, F; Bellia, C; Giardina, A; Raffa, A; Ciaccio, M; Pinto, A
Abstract : Objective: The aim of this study was to investigate the relationship between immunoinflammatory markers and indexes of arterial stiffness in patients with seronegative spondyloarthritis (SpA). Method: We enrolled consecutive patients with inflammatory seronegative SpA referred to a rheumatology outpatient clinic. Control subjects were patients admitted in the same period for any cause other than chronic inflammatory disease or acute cardiovascular and cerebrovascular events. Carotid-femoral pulse wave velocity (PWV) was measured and the aortic pressure waveform was used to calculate the augmentation index (Aix). We also evaluated plasma levels of C-reactive protein (CRP), interleukin (IL)-1β, tumour necrosis factor (TNF)-α, and interleukin (IL)-6 as markers of immunoinflammatory activation. Results: This study enrolled 53 patients with SpA and 55 control subjects. After adjustment for blood glucose, cholesterol, and triglyceride levels, and systolic (SBP) and diastolic blood pressure (DBP), patients with seronegative SpA showed higher mean PWV and Aix compared to controls. Moreover, in patients with seronegative SpA, we observed higher mean plasma levels of IL-6, IL-1β, and TNF-α in subjects with mean PWV > 8 m/s in comparison with those with PWV < 8 m/s. Multivariate analysis revealed a significant association between PWV > 8 m/s and male gender, age, diabetes, hypertension, low density lipoprotein cholesterol (LDL-C) > 120 mg/dL, total cholesterol (TC) > 200 mg/dL, coronary artery disease (CAD), microalbuminuria, carotid plaque, and plasma levels of IL-6, IL-1β, and TNF-α. Conclusions: These findings emphasize the role of inflammatory variables and metabolic factors in indexes of high arterial stiffness. Thus, an inflammatory-metabolic background may influence the pathogenesis of increased arterial stiffness in seronegative inflammatory arthritis.